Anaphase‐promoting complex/cyclosome‐Cdc‐20 promotes Zwint‐1 degradation. (16th January 2020) - He, Yan; Li, Rui; Gu, Liming; Deng, Huixiong; Zhao, Ying; Guo, Yingzhu; Yu, Shun; Wang, Gefei
Abstract : ZW10 interactor (Zwint‐1) is an important component of the centromere and can recruit the dynamic protein kinase and dynein to promote chromosome movement and regulate the spindle assembly checkpoint (SAC). Zwint‐1 activity is tightly regulated during the cell cycle. However, how the stability of Zwint‐1 is regulated has not been clarified. Here, we show that the relative levels of Zwint‐1 expression gradually decreased with the progression of cell cycling and decline sharply during mitotic exit. Treatment with cycloheximide reduced the levels of Zwint‐1 while treatment with MG132 to inhibit endogenous ubiquitin‐proteasome elevated the levels of Zwint‐1 in HEK293T cells or Hela cells. Such data suggest that Zwint‐1 may be degraded by endogenous ubiquitin‐proteasome. Furthermore, induction of cell‐division cycle protein 20 (Cdc20) overexpression decreased the levels of Zwint‐1, which was abrogated by MG132 treatment. In contrast, Cdc20 silencing promoted the accumulation of Zwint‐1. in vivo ubiquitination assay revealed that Cdc20 promoted the formation of Zwint‐1 and ubiquitin‐proteasome conjugates. Cotransfection with Cdc20 and wild‐type Zwint‐1, but not Zwint‐1 ΔD‐box, reduced the levels of Zwint‐1. Immunoprecipitation and western blot analyses showed that Cdc20 interacted with wild‐type Zwint‐1, but not Zwint‐1 ΔD‐box although both Zwint‐1 and Zwint‐1 ΔD‐box overexpression did not induce mitotic arrest. Collectively, our data indicated that Zwint‐1 was ubiquitinated by anaphase‐promoting complex/cyclosome (APC/C)‐Cdc20 in a D‐box‐dependent manner. Therefore, the APC/C‐Cdc20 controls the stability of Zwint‐1, ensuring accurate regulation of the spindle assembly during the cell cycling in HEK293T cells.